2016
DOI: 10.1289/ehp.1408483
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollution Exposure during Pregnancy and Childhood Autistic Traits in Four European Population-Based Cohort Studies: The ESCAPE Project

Abstract: BackgroundPrenatal exposure to air pollutants has been suggested as a possible etiologic factor for the occurrence of autism spectrum disorder.ObjectivesWe aimed to assess whether prenatal air pollution exposure is associated with childhood autistic traits in the general population.MethodsOurs was a collaborative study of four European population-based birth/child cohorts—CATSS (Sweden), Generation R (the Netherlands), GASPII (Italy), and INMA (Spain). Nitrogen oxides (NO2, NOx) and particulate matter (PM) wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
87
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 102 publications
(92 citation statements)
references
References 32 publications
3
87
1
1
Order By: Relevance
“…Meta-analysis studies support the involvement of particulate matter or ambient air pollution in relation to autism in North American [81,309] but not European studies [87] and for the prenatal uses of SSRI's [310] or Vitamin D deficiency in autistic patients [311] but the diverse methodologies used to measure timing and exposure have rendered clear conclusions difficult for these and others such as phthalate esters [312]. These problems are confounded by the gene/environment interactions raised in this study (i.e.…”
Section: Ecological Pollution and Bioaccumulationmentioning
confidence: 64%
“…Meta-analysis studies support the involvement of particulate matter or ambient air pollution in relation to autism in North American [81,309] but not European studies [87] and for the prenatal uses of SSRI's [310] or Vitamin D deficiency in autistic patients [311] but the diverse methodologies used to measure timing and exposure have rendered clear conclusions difficult for these and others such as phthalate esters [312]. These problems are confounded by the gene/environment interactions raised in this study (i.e.…”
Section: Ecological Pollution and Bioaccumulationmentioning
confidence: 64%
“…An increased odds of ASD diagnosis was reported in Jung et al in relation to postnatal exposure to CO, NO 2 , O 3 , and SO 2 (40). However, 2 other studies in Europe encountered no association between prenatal exposure to NO 2 and PM 2.5 or PM 10 with autistic traits (41) or between pre-and postnatal exposure to NO x , PM 10 , and ASD (42).…”
Section: Autism Spectrum Disorder (Asd)mentioning
confidence: 82%
“…Boggess et al (2016) pooled heavy metals and organic pollutants into a single variable of xenobiotic exposure and reported that xenobiotic exposure level correlated with severity of ASD communication impairment (p = .02) and ASD social impairment severity (p = .05). Conversely, Guxens et al (2015) found no link between prenatal air pollution and ASD in a study of 8000 children. Volk et al (2014), however, demonstrated that if individuals homozygous for the C allele of the MET gene were exposed to air pollution, they had an increased ASD risk rate of 2.9 (1.0-10.6).…”
Section: Environmental Syndromic Asd Has Been Found With Varied Brainmentioning
confidence: 93%